Form, figure, and the experience of tíme in seven southern composers of the 1950S-60S - Vallauri, Stefano Lombardi (Interdisciplinary Studies in Musicology, 2018)
After the 1980s it is difficult, following stylistic criteria, to draw a map of contemporary academic music. All styles are compossible, and all are practiced. In this context, the geographical entity “South of Italy” does not stand out for a musical identity with special technical-stylistic features. Rather, at a socio-cultural level, the South remains today - in music no less than in all areas where there is a gap between top development and stagnation - a land of emigrants: six out of the seven composers treated (Ivan Fedele, Giuseppe Colardo, Rosario Mirigliano, Giuseppe Soccio, Nicola Cisternino, Biagio Putignano, Paolo Aralla) live in the North of Italy. The positive aspect of this is the affinity of the South with the transnational and superstructural community of contemporary music, which from European and Western has now become almost global. The composers under consideration belong to the generation of the ‘50s, rooted in the serial and post-serial movements (from which Franco Donatoni, Luciano Berio, Luigi Nono, Salvatore Sciarrino, Giacinto Scelsi, are the principals models, to mention only the Italians), dipped in the general phenomenon of timbrism (particularly spectralism), and acquainted with electronics. They draw from these sources various instruments of compositional technique and aspects of their poetics. In particular these composers, active from the ‘80s, develop new ways of construction of the temporal form of music. They share the goal to establish a new continuity, different from the tonal one but at the same time transcending the serial and post-serial disintegration and fragmentation. The primary means to this end is a new enhancement of the ( ategory of figure, as a clear and distinct, recognizable aggregate of pitches, intervals, register, duratio is, timbre, articulation, dynamics, and texture. Each composer elaborates the atonal figurai material in different ways, emphasizing one aspect or another. For example, Fedele (1953) is a master in the management of form per se, Colardo (1953) in the activation of disturbed harmonic effects, Mirigliano (1950) in the creation of a slight tension from the smallest vibrations of sound, Soccio (1950) in the set up of movement by means of accumulations and discharges of energy, Cisternino (1957) in a Cagean-Scelsian emphasis on sound as such, Putignano (i960) in the suspension of time through the succession and transformation of images, Aralla (i960) in the foundation of form from below, from the concreteness of sound.